2021
DOI: 10.3389/frvir.2021.719681
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Immersive Virtual Reality on Pain and Anxiety at a Veterans Affairs Health Care Facility

Abstract: Objectives: The primary objective of this evaluation is to determine the impact of virtual reality (VR) distraction on acute and chronic pain in Veterans within the Veterans Affairs Health Care System (VA). A secondary objective is to determine the impact of VR on the experience of stress and anxiety in Veterans utilizing VR for the indication of pain. A third objective is to develop an understanding of the Veteran experience of using VR in a healthcare setting.Methods: This prospective, pretest-posttest mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Thus, studies have found that VR-based training can be effective in improving motor function, balance, and mobility in individuals who have had a stroke, as well as cognitive function in those with brain injury and other neurological conditions (Kumar et al, 2018;Chen et al, 2021). VR-based training has also been shown to have positive effects on psychological well-being, such as reducing anxiety and depression in individuals with chronic pain (Rawlins et al, 2021). Therefore, VR-based training has the potential to enhance the effectiveness of various interventions in healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, studies have found that VR-based training can be effective in improving motor function, balance, and mobility in individuals who have had a stroke, as well as cognitive function in those with brain injury and other neurological conditions (Kumar et al, 2018;Chen et al, 2021). VR-based training has also been shown to have positive effects on psychological well-being, such as reducing anxiety and depression in individuals with chronic pain (Rawlins et al, 2021). Therefore, VR-based training has the potential to enhance the effectiveness of various interventions in healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…VR distraction can also temporarily reduce chronic pain (Wiederhold et al, 2014;Rawlins et al, 2021) and we predict may temporarily reduce chronic pain during PT/OT sessions. And that may help increase patient's compliance with the therapists.…”
Section: The Innovative Use Of Mirror Therapy For Treating Chronic Painmentioning
confidence: 77%
“…Virtual Reality is so intuitive that even patients who are new to technology are often surprisingly receptive to using virtual reality. And recent research shows that a positive experience in VR made veterans more open to trying other non-pharmalogic treatments that they had previously not been willing to try (Rawlins et al, 2021).…”
Section: Chronic Pain In Veteransmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 , 3 Over the last 2 decades, VR has been explored as a resource to enhance patient care in the medical setting as a distraction therapy for pain and anxiety. 4 Humans have finite attentional resources; therefore, it is believed that distracting them with a task leaves less cognitive capacity for processing negative emotions and stimuli. Virtual reality has been effective as a distraction technique in a variety of wide-awake procedures, including chemotherapy administration, needle sticks, burn care, cutaneous procedures, and dentistry.…”
mentioning
confidence: 99%